English-Speaking Learning for Fifth-Grade Elementary School Students Using a Contextual Learning Model Assisted by Flashcards - Kurniati, Erisa; Kumalasari, Ade (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to increase students’ speaking ability by using flashcard props (picture cards). The method used is qualitative. The sample of this research is the students of class V SDN 205/IV Jambi, Academic Year 2022/2023. The results showed an increase in English speaking skills, which refers to the results of the final test and interviews given to students. Thus, the use of contextual learning models assisted by flashcards can improve the English speaking skills of students in class V SDN 205/IV Jambi.